1925 Mich. Pub. Acts 473 - (:unkn) unknown (My University, 1925)
An Act to Regulate the Possession and Sale of Pistols, Revolvers and Guns; to Provide a Method of Licensing Those Carrying Such Weapons Concealed; and to Provide Penalties for Violations of Such Regulations, § 2-4:§Any person who shall commit or attempt to commit a felony when armed with a pistol, revolver or gun, as defined in section one, shall, in addition to the punishment provided for committing the crime, be punished by imprisonment for not less than two nor more than five years within the discretion of the court.
Keywords: COMMITTING CRIME W/ WEAPON